Flood Routing in Rivers Using Two-Dimensional HEC-RAS Software and its Comparison with the Non-Linear Muskingum Method - M. Amiri; E. Fazel Najafabadi; M. Shayannejad (علوم آب و خاک)
One of the important issues in river engineering is flood trends. In general, two types of methods are used to determine the flood trends in rivers. The first group of hydraulic methods, such as the dynamic wave method, is based on solving continuity and momentum equations or Saint-Venant equations. The second category is hydrological methods like the non-linear Muskingum method. In this research, both methods have been used to determine the trends of flood hydrographs in the Plasjan River, one of the main tributaries of the Zayandehrud River. The coefficients of the non-linear Muskingum method were obtained by optimizing and solving the related equation with the fourth-order Runge-Katai numerical method using MATLAB software and the dynamic wave method using the two-dimensional HEC-RAS software. In this study, four flood events were used. In the non-linear Muskingum method, the first event was used for model calibration and the other three events were used for validation. The error rate in this method for the second, third, and fourth events was 84.23, 6.6, and 7.96 percent, respectively, and the error rate in the dynamic wave method for these four events was 17.58, 87.3, 5.4, and 6.21 percent, respectively. Therefore, the dynamic wave method is more accurate in estimating the output hydrograph. However, the non-linear Muskingum method has acceptable accuracy and is recommended in terms of cost, required information, simplicity, and speed of calculation in situations where sufficient information is not available.